Penerapan Sanksi Pidana Tambahan Kebiri Kimia Ditinjau dari Perspektif Keadilan - Adella Aldionita Chairi; Ivan Zairani Lisi; Rini Apriyani (Fakultas Hukum Universitas Mulawarman, 2020)
In Indonesia, cases of sexual violence against children are serious crimes. Law Number 17 the Year 2016 concerning Establishment of Government Regulation in place of Law (PERPPU) Number 1 the Year 2016 concerning Second Amendment to Law Number 23 the Year 2002 concerning Child Protection, which can be picked up following chemical castration. The author has two objectives, first about the additional legal requirements for chemical castration in terms of the perspective of justice against victims, the second to provide clarity on the additional innocence of chemical castration in Law Number 17 of 2016 concerning the Establishment of PERPPU Number 1 of 2016 in children The granting of additional castration chemical crime law from the perspective of justice against victims is a form of retaliation for the crime. Nothing in Law Number 17 of 2016 concerning the Establishment of PERPPU Number 1 of 2016 has the objective to be achieved is to protect the nation's children and become material for judges in opposing penalties against violence against children.